A survey study on evaluation and management of nocturnal enuresis in pediatricians and family physicians - ŞEKERCİ, ÇAĞRI AKIN; KÜTÜKOĞLU, MEHMET UMUT; DÖRÜCÜ, DOĞANCAN; TANIDIR, YILÖREN; ÇAM, HAYDAR KAMİL; TARCAN, TUFAN; YÜCEL, SELÇUK (My University, 2023)
Objective:Nocturnal enuresis (NE) is one of the most common disorders in pediatric urology, and patients often turn to family physicians (FP) and pediatricians (P) initially. The aim of this study was to understand the awareness, self-confidence and suggestions of physicians regarding the management of NE.Materials and Methods:In this study, 360 FP and family medicine residents (FMR), as well as 280 P and pediatrics residents (PR), were contacted through a cellular phone texting system. A simple multiple-choice questionnaire (Surveymonkey®) consisting of 10 questions was used to gather data. The survey included questions about their experience, training, evaluation, and management of NE.Results:A total of 119 FPs and Ps (18.5%) filled the questionnaire. Thirty (25.21%) of the participants were P, 27 (22.69%) PR, 3 (2.52%) FP and 59 (49.58%) FMR. The rate of physicians who encounter at least 5 children with NE per month is 31.33%. The mean self-confidence in the management of NE was 4.5 out of 10. The self-confidence of pediatricians was significantly higher than that of PR and FMR (p<0.001, p<0.001). Most (n=78, 65.55%) of the participants stated that they received training on EN during medical faculty and 62 (52.10%) during residency. Psychological problems (89.92%), sleep disorders (78.15%), and excessive fluid intake (75.63%) were the most frequently considered factors in etiology. While most responders (75.63%) considered dietary regulation and behavioral interventions as the first-line treatment, 25.21% consult a pediatric urologist and only 1.6% recommend medical treatment.Conclusion:Although FP and P admit they had training on NE, they mostly felt incompetent to manage NE and exclusively avoided pharmacological treatment.Keywords:Children, enuresis nocturna, pediatric urology, physicians, survey
Keywords: Tıp; Cerrahi Tıp Bilimleri; Üroloji; Pediatrik Üroloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Urology; Pediatric Urology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; SURGERY; Cerrahi; Nefroloji; Surgery; Nephrology; Children; enuresis nocturna; pediatric urology; physicians; survey